COMPARATIVE EFFICACY OF ACE INHIBITORS VS. ARBS IN THE MANAGEMENT OF HYPERTENSION AND HEART FAILURE - NAWAZ, NK; KHAN, SI; KAMAL, R; ISMAIL, T; UDDIN, MA; ADNAN, SH; SIDDIQUI , FI; IQBAL, N (Biological and Clinical Sciences Research Journal, 2024)
Angiotensin-converting enzyme inhibitors (ACE inhibitors) and angiotensin II receptor blockers (ARBs) are two classes of medications widely used to treat hypertension and heart failure. Objective: The study aims to find the comparative efficacy of ACE inhibitors vs. ARBs in managing hypertension and heart failure. Methodology: This comparative observational study was conducted at Mirpur University of Science and Technology MUST, Azad Kashmir, from January 2023 to December 2023. The study included 85 patients diagnosed with either hypertension, heart failure, or both. Baseline characteristics such as age, gender, and comorbidities were recorded for each patient to ensure a balanced comparison between those treated with ACE inhibitors and those treated with ARBs. Both groups showed significant reductions in blood pressure, with ACE Inhibitors leading to a mean systolic decrease of 15.2 mm Hg and a diastolic reduction of 9.8 mm Hg, compared to 14.7 mm Hg and 9.4 mm Hg, respectively, for ARBs. However, the differences between the groups were not statistically significant (p > 0.05).Results: Data were collected from 85 patients. The average age was approximately 65 years in both groups. Gender distribution was nearly equal, with males comprising 48% of the ACE Inhibitors group and 49% of the ARBs group, while females comprised 52% and 51%, respectively. Diabetes was slightly higher in the ACE Inhibitors group (36%) than in the ARB group (33%). Conclusion: Both ACE inhibitors and ARBs are equally effective in managing hypertension and heart failure, with similar efficacy in reducing blood pressure and improving heart failure symptoms.